Automaticity Componential causal, and mechanistic explanations. [article]. - Moors, Agnes
The review first discusses componential explanations of automaticity, which specify non/automaticity features (e.g. un/controlled, un/conscious, non/efficient, fast/slow) and their interrelations. Reframing these features as factors that influence processes (e.g., goals, attention, and time) broadens the range of factors that can be considered (e.g., adding stimulus intensity and representational quality). The evidence review challenges the view of a perfect coherence among goals, attention, and consciousness, and supports the alternative view that (a) these and other factors influence the quality of representations in an additive way (e.g. little time can be compensated by extra attention or extra stimulus intensity) and that (b) a first threshold of this quality is required for unconscious processing. The review closes with a discussion of causal explanations of automaticity which specify factors involved in automatization such as repetition and complexity, and a discussion of mechanistic explanations, which specify the low-level process underlying automatization. -- (from the author)
Keywords: Conscious; Depression; Control; Attention; Representation; Practice; Complexity